4CPS-065 Clinical impact evaluation of implementing antibiotherapy control of more than 7 days. (March 2019) - Moutaouakkil, Y; Tadlaoui, Y; Atbib, Y; Adouani, B; Bennana, A; Cherrah, Y; Lamsaouri, J; Bousliman, Y
Abstract : Background: Bacterial resistance is a major preoccupation and the correct use of antibiotics is a global public health priority. 1 The inappropriate use of antibiotics, particularly the increase in duration, can have serious consequences in terms of ecological and pharmaco-economic factors. Purpose: The study aim was to set up a systematic control of antibiotherapy exceeding 7 days by evaluating its impact. Material and methods: From January to June 2018, all curative antibiotherapy up to 7 days have been detected by the pharmacist. The expected treatment durations were all re-evaluated, in consultation with the initial prescriber, according to the clinical situation and the recommendations and data available on treatment durations. Results: A total of 97 antibiotic treatments prescribed for more than 7 days have been re-evaluated. The indications were mainly osteoarticular (n=14), urinary (n=24), pulmonary (n=15), skin and soft tissue (n=18), digestive (n=22) and endocarditis (n=22)=4). The expected duration was justified in 78 cases (80.41%) and could be shortened in 19 cases (19.58%). For the latter, 15 (15.46%) involved urinary tract infections and four (4.12%) pulmonary infections. Prescribers accepted the shorter duration proposal in 17 cases, an acceptance rate of 89.47%. For these patients, the median duration of treatment increased from 14 days (originally planned duration) to 8 days (actual duration). In total, 105 days of antibiotic therapy were saved. Regarding the 17 patients whose duration was shortened after surgery, the clinical course was favourable for all patients and no adverse effects were observed. Conclusion: The establishment of the antibiotherapy control of more than 7 days, by the pharmacist, can make it possible to reduce the duration of treatment and to decrease the frequency of the undesirable effects, without an impact on the clinical evolution of the patients. References and/or acknowledgements: 1. Moutaouakkil Y, Siah S, Bennana A, et al. Réévaluation clinico-biologique de l'antibiothérapie probabiliste en réanimation des brules. Ann Burns Fire Dis 2018;31:35. No conflict of interest.